Linking environment, democracy and gender - Wejnert, Barbara (Research in political sociology ;, 2012)
This volume highlights the ways in which scholarly analysis has contributed to a rich understanding of the links between spreading democracy, gender equality, and environmental protection. Combining theoretical, empirical, and policy perspectives, the volume includes cutting-edge debates on the meaning of democracy and the processes of its development, as well as the response of democracies to environmental and gender concerns. In particular, the volume answers questions applicable to the situation of women in the democratizing world as well as to environmental problems, linking together the issues of gender and environment. It discusses the difference between democratic and non-democratic countries in terms of protection and care for their citizens; security of women's rights and women's opportunities offered by democratic vs. non-democratic states; relations between environmental issues and gender; and women's response to environmental problems.